THE EFFECTS OF ENGINEERING DESIGN-BASED MATHEMATICS APPLICATIONS ON SPATIAL ABILITIES AND 3D GEOMETRICAL THINKING SKILLS OF STUDENTS WITH DIFFERENT LEARNING APPROACHES - (:unkn) unknown (My University, 2021)
Design activities help students develop their three-dimensional thinking skills and gain engineering and technology literacy. This study investigated whether the spatial abilities and 3D geometrical thinking skills of the students differed according to approaches to learning mathematics before and after engineering design-based mathematics (EDBM) applications. Seventy-five eighth-grade students from a public middle school participated in the study. Data were collected with 3D Geometrical Thinking Test (3DGTT), Spatial Ability Test (SAT) and Approaches to Learning Mathematics Scale (ALMS). In the research, quasi-experimental design with pre-test and post-test control group was used. Engineering design-based mathematics activities were carried out an eight-week period, while the control group received mathematics instruction in line with traditional teaching methods. The results of the study showed that the spatial abilities of the students differed according to the approaches to learning mathematics, whereas the 3D geometrical thinking skills of the students did not differ